Quercitrin Stimulates Hair Growth with Enhanced Expression of Growth Factors via Activation of MAPK/CREB Signaling Pathway - Jaeyoon Kim; Soon Re Kim; Yun-Ho Choi; Jae young Shin; Chang Deok Kim; Nae-Gyu Kang; Byung Cheol Park; Sanghwa Lee (Molecules, 2020)
The present study aimed to investigate the molecular mechanism of quercitrin, a major constituent of Hottuynia cordata extract, for its hair growth stimulating activities in cultured human dermal papilla cells (hDPCs). Quercitrin enhanced the cell viability and cellular energy metabolism in cultured hDPCs by stimulating the production of NAD(P)H and mitochondrial membrane potential (ΔΨ). The expression of Bcl2, an essential marker for anagen hair follicle and cell survival, was increased by quercitrin treatment. Quercitrin also increased the cell proliferation marker Ki67. The expression of growth factors—such as bFGF, KGF, PDGF-AA, and VEGF—were increased by quercitrin both in mRNA and protein levels. In addition, quercitrin was found to increase the phosphorylation of Akt, Erk, and CREB in cultured hDPCs, while inhibitors of MAPKs reversed the effects of quercitrin. Finally, quercitrin stimulated hair shaft growth in cultured human hair follicles. Our data obtained from present study are in line with those previously reported and demonstrate that quercitrin is (one of) the active compound(s) of Hottuynia cordata extract which showed hair growth promoting effects. It is strongly suggested that the hair growth stimulating activity of quercitrin was exerted by enhancing the cellular energy metabolism, increasing the production of growth factors via activation of MAPK/CREB signaling pathway.